Evaluation of wireless home automation technologies for smart mining camps in remote western australia - Rathnayaka, Dinusha; Potdar, Vidyasagar; Kuruppu, S. (Springer, 2011)
Remote Western Australian (WA) is featured with harsh environmental and living conditions, but extremely rich soil with large mineral deposits. Mining companies have invested immensely in those areas, and mining camps have been constructed with thousands of Single Person Quarter (SPQ) units to fulfill mining worker accommodation. Major challenge faced by SPQ suppliers is improving the quality of life of the workers, while minimizing the energy cost. In recent years, Wireless Home Automation (WHA) has become an ideal choice for SPQs to achieve these targets. In this paper we perform one of the initial steps of the feasibility study of integrating WHA to SPQs. Generally in a WHA network, wireless sensors and actuators intelligently interconnect with each other through a suitable WHA technology. This paper evaluates different WHA technologies to find out the most suitable technology to implement WHA specifically for SPQs based on the practical requirements outlined by our industry collaborator, who is an Australian mobile accommodation company, supplying smart SPQs to mining camps.